SAT0099 Contribution of disease activity, joint damage and comorbidity to impairment and disability in rheumatoid arthritis patients during 20 years. (23rd January 2014) - Crnkic Kapetanovic, M.; Lindqvist, E.; Nilsson, J.-Å.; Geborek, G.; Saxne, T.; Eberhardt, K.
Abstract : Objectives: To study the contribution of disease activity, joint damage and co-morbidity on development of impairment measured by signals of functional impairment (SOFI) and disability measured by health assessment questionnaire (HAQ) in rheumatoid arthritis (RA) patients prospectively followed over 20 years after diagnosis. Methods: 183 RA patients diagnosed between 1985 and 1989 were prospectively monitored over 20 years. Treatments followed clinical practice. There were 115 (63%) women, mean (SD) age was 52 (12) years and symptom duration before inclusion was 11 (7) months. Disease activity was measured by 44-joint DAS, joint damage by Larsen score of radiographs of hands and feet, comorbidity by Charlson Comorbidity Index (17 diagnoses each weighted by mortality risk), impairment by SOFI (a 3-parts performance based index measuring hand, arm and leg function) and disability by HAQ. Two separate multiple regression models with SOFI and HAQ as outcome variables at 0, 5, 10, 15 and 20 year follow up were created (table ). Results: Altogether, disease activity, radiographic joint damage and comorbidity explained 22-38% (maximum at 15 yeas) of SOFI and 17-38% (maximum at 5 years) of HAQ. HAQ and SOFI correlated moderately (Spearman's rho 0.46-0.72). For SOFI, DAS contributed between 2 and 27% with a peak at 5 years. Radiographic damage contributed increasingly (6-35%) whereas comorbidity only had low to moderate occasional contribution (0-5%) (table ). For HAQ, DAS contributed at all follow up times (7-28%), with a peak at 5 years. Radiographic damage showed only a minor contribution (0-10%) with maximum at 15 years, whereas comorbidity contributed only up to 10 years (0-7%) (table ). Conclusions: In the long-term perspective impairment is increasingly explained by radiographic damage, whereas disability is less well explained by RA related factors over time. Comorbidity contributed only to a small extend to both impairment and disability. Disclosure of Interest: None Declared